Evaluation of thermal properties of bamboo/kenaf fiber reinforced epoxy hybrid composites and nanocomposites - Chee, Siew Sand (2020)
The awareness of environmental concerns has increased the need to produce high performance engineering materials with natural fiber-based materials. Hybridizing natural fibers with nanofiller modified polymeric composites is a potential alternative material that displays better mechanical and thermal properties for advanced applications. This research work focussed on the evaluation of the hybridization effects between non-woven bamboo mat (B) and woven kenaf mat (K) reinforced epoxy hybrid composites with further enhancement on the thermal properties by adding nanoclay. The hybrid composites were prepared by hand lay-up techniques. The epoxy/nanoclay mixture was prepared by in-situ polymerization by using a high shear speed homogenizer. Optimum fiber mixing ratio (B/K:30/70, B/K:50/50; B/K:70/30) were examine in terms of their thermal properties and resistance against environmental effects. The results reveal that increasing the bamboo fiber loading improved the thermal stability of the hybrid composites. The initial decomposition temperature of B/K:70/30 is about 10 ℃ higher than kenaf/epoxy composite. B/K:50/50 hybrid composites exhibit the highest dimensional stability and viscoelastic behaviour. It recorded the lowest thermal expansion percentage (1.14%) while B/Epoxy and K/Epoxy recorded the total thermal expansion at 2.33% and 1.47%, respectively. Besides, the durability of the hybrid composites against environmental effects was also studied by accelerated weathering test and soil burial test. B/K:50/50 hybrid composites presents a balance of resistance to environmental effects while maintaining the biodegradability characteristic. The organoclay loading (0.5, 1.0, 2.0, 4.0wt.%) epoxy nanocomposites were fabricated. The morphological, thermal, dynamic mechanical and tensile properties of the nanocomposites show optimum performance at 1wt.% loading. Further study was carried out by fabricating B/K/Nanoclay/Epoxy hybrid nanocomposites with bamboo and kenaf fiber ratio was fixed at 50:50 and nanoclay loading was fixed at 1wt.%. The effects on adding 3 different types of nanoclays: halloysite nanotube (HNT), montmorillonite (MMT) and organically modified MMT (OMMT) were compared. The morphological, thermal and flammability of the B/K/Nanoclay/Epoxy hybrid nanocomposites were characterized. The morphological study reveals that MMT/Epoxy and HNT/Epoxy are highly agglomerated while OMMT/Epoxy reveals a more uniform distribution morphology. The oxidative decomposition behaviour of the hybrid composites was studied with a thermogravimetry analyzer (TGA) under an oxygen atmosphere. The flammability properties were evaluated through Underwriters Laboratories 94 horizontal burning test (UL-94HB), limiting oxygen index (LOI), cone calorimetry and smoke density tester. The final decomposition temperature of B/K/OMMT recorded at 495 °C and it is 60 °C higher compare to B/K/Epoxy. The residue value of the hybrid nanocomposites at 800 ℃ is significantly increased by 196%, 175%, 269% with the addition of MMT, HNT and OMMT nanoclay, respectively. All hybrid nanocomposites achieved an HB40 rating in the UL-94HB test. With the addition of nanoclay, the LOI value increased from 20 to 28%. A significant reduction of total heat release and peak heat release rate between 36 – 43% was observed on nanoclay filled hybrid composites. Improvement of other fire indicators such as FIGRA (fire growth rate index), MARHE (maximum average rate of heat emission) and SMOGRA (smoke growth rate index) were noticed in all hybrid nanocomposites with excel performance observed on B/K/OMMT. The findings from this work can be utilized in preparing high-performance natural fibers reinforced epoxy hybrid composites with improvement in their dimensional stability and fire performance for automotive and building applications.